Art Encounters Deleuze and Guattari - O'Sullivan, S. author. aut Link
XIV, 230 p.
Keywords: In a series of philosophical discussions and artistic case studies, this volume develops a materialist and immanent approach to modern and contemporary art. The argument is made for a return to aesthetics - an aesthetics of affect - and for the theorization of art as an expanded and complex practice. Staging a series of encounters between specific Deleuzian concepts - the virtual, the minor, the fold, etc. - and the work of artists that position their work outside of the gallery or 'outside' of representation - Simon O'Sullivan takes Deleuze's thought into other milieus, allowing these 'possible worlds' to work back on philosophy.